Evolution Sucks (London Journal of Research In Science: Natural and Formal, 2025)
The article deals with evolution and the environment. I assume the unproven claim that all life is generated through evolution. In the chapter titled Evolution Sucks I demonstrate that it can have sometimes negative consequences. Although there is no alternative academic explanation, I illustrate some of the disadvantages of Darwins theory.In the final chapter The Glut Society I reference some older books on climate change and the environment in general.